(39+Х)-27=22 44-(22+Х)=22 78-16-Х=41

(39+Х)-27=22 44-(22+Х)=22 78-16-Х=41
Гость
Ответ(ы) на вопрос:
Гость
1) (39+Х)-27=2239 + x = 22 + 27;x = 49 - 39;x = 10;2) 44-(22+Х)=2222 + x = 44 - 22;x = 22 - 22;x = 0;3) 78-16-Х=41 x = 78 - 16 - 41;x = 21;
Гость
1)   (39+х) -27=22       39+х -27=22       х= 22+27 -39       х= 10 2)    44-(22+х)=22        44 -22 -х=22        -х= 22+22-44        х=0 3)   78 -16 -х=41        -х= 41+16 -78        -х= -21         х=21. 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы